Layer-by-Layer of Thin Films of Nickel Hexacyanoferrate Multilayer Anchored to Self-Assembled of Mercaptoacetic Acid - Qu, Jianying; Wang, Shumin; Chen, Wenjing (Asian Journal of Chemistry, 2010)
A general methodology to prepare redox active inorganic mutilayers consisting of nickel hexacyanoferrate layers formed by layer-by-layer assembly was constructed. The layers were anchored through mercaptoacetic acid on gold electrode. The electrochemical characteristics of nickel hexacyanoferrate modified electrode in the presence of different ions (K+, Na+, Cl–, Br– and F–) were investigated by cyclic voltammetry and exhibited a near-Nernstian with a slope of 54 mV/decade to potassium ions in the range from 1 × 10-2-1 mol/L, which can be use as potential sensor to determine concentration of potassium ion. The modified electrodes showed good stability.